Fluorescent Aptasensor for Highly Specific Detection of ATP Using a Newly Screened Aptamer - Xin Chen; Yangkun Feng; Haohan Chen; Yuting Zhang; Xiaoli Wang; Nandi Zhou (Sensors, 2022)
Owing to the significant roles of adenosine triphosphate (ATP) in diverse biological processes, ATP level is used to research and evaluate the physiological processes of organisms. Aptamer-based biosensors have been widely reported to achieve this purpose, which are superior in their flexible biosensing mechanism, with a high sensitivity and good biocompatibility; however, the aptamers currently used for ATP detection have a poor ability to discriminate ATP from adenosine diphosphate (ADP) and adenosine monophosphate (AMP). Herein, an ATP-specific aptamer was screened and applied to construct a fluorescent aptasensor for ATP by using graphene oxide (GO) and strand displacement amplification (SDA). The fluorescence intensity of the sensor is linearly related to the concentration of ATP within 0.1 μM to 25 μM under optimal experimental conditions, and the detection limit is 33.85 nM. The biosensor exhibits a satisfactory specificity for ATP. Moreover, the experimental results indicate that the biosensor can be applied to determine the ATP in human serum. In conclusion, the screened aptamer and the biosensor have promising applications in the determination of the real energy charge level and ATP content in a complex biological system.